Development of Vanadium Phosphate Catalyst using Microwave Technique to Oxidize n-Butane Into Maleic Anhydride - Tang, Lok Hing (2010)
New VPO catalysts were prepared via microwave method. Comparison of these catalysts with those from conventional reflux method on the microstructure, morphology, oxygen nature and catalytic performance for n-butane oxidation to maleic anhydride are described and discussed. The catalyst’s precursor, VOHPO·0.5H20 prepared by reduction of VOPO4·2H2O by isobutyl alcohol under microwave irradiation exhibited similar pattern with conventional catalysts and more crystalline, which was indicated by high intensity of the peaks in XRD. It is interesting that the use of the microwave had significantly shorten the duration (<1 h) in the preparation of the precursor compared to 22 h normally used in the conventional method. Temperature-programmed reduction (TPR) in H2 resulted two reduction peaks which were observed in the range of 600-1100 K. The present work demonstrated that the influence of microwave irradiation on vanadium phosphate catalysts effectively enhanced the catalytic activity and selectivity for the oxidation of n-butane to maleic anhydride which contributed by the higher BET surface area and the higher amount of active and selective oxygen species removed from V4+ and V5+ phases, respectively. Mechanochemical treatment applied on vanadium phosphate (VPO) catalyst’s precursor, VOHPO40.5H2O prepared by the reduction of VOPO42H2O with isobutanol under microwave irradiation, was subjected to a high energy ball mill for 60 min in ethanol as solvent. The treatment increased the average oxidation number of catalysts without changing the phase composition. The particle sizes of catalysts decreased after the ball milling process. The morphologies of milled catalysts are dependent on milling time. The surface area of milled catalysts decreased due to the time applied of ball milling on precursor was longer. High mobility of the lattice oxygen species has been achieved for milled catalysts with higher amount of oxygen atoms removed. A good correlation was shown between the oxygen (O-) species associated with V4+ and n-butane conversion. A good correlation between n-butane conversion and V4+ phase can be observed. The reactive pairing of V4+-O- was suggested to be the center for n-butane activation. However, a large amount of oxygen species removed from V5+ would give a deleterious effect on the conversion rate. The present study showed that the mechanochemical method has effectively enhanced the microwave synthesized catalysts on the catalytic activity by increasing n-butane conversion and maintaining the MA selectivity. Nd-doped (1, 3, and 5 %) vanadium phosphate (VPO) catalysts were prepared by including an introduction of microwave irradiation in the synthesis of VOPO4·2H2O. The dopant, Nd (in nitrate form) was added during the refluxing of VOPO4·2H2O with isobutanol. The precursors and catalysts were characterized using XRD, BET, redox titration, SEM and H2-TPR to obtain the linkage information of catalytic behavior of the solids with their physicochemical properties.The catalytic test was carried out at 673 K (2400 h-1) in a microreactor by flowing a mixture of n-butane/air. The present work demonstrated that the addition of Nd dopants to VPO catalysts increased the catalytic performance significantly compared to the undoped VPO catalysts. TPR analysis showed that the reduction behaviour of Nd-doped catalysts was dominated by reduction of V4+ and V5+ species. An excess of the oxygen species (O2-) associated with V5+ in Nd-doped catalysts improved the maleic anhydride selectivity but reduced the conversion rate of n-butane. Good correlation obtained on the n-butane conversion versus the amount of oxygen (O-) removed associated with V4+ and amount of V4+ phase. The reactive pairing of V4+-O- was shown to be a centre for n-butane activation in agreement to earliest findings. Among the catalysts tested, an addition of 3 % Nd (VPDNd3) in VPO catalyst gave the highest n-butane conversion (75 %) and MA selectivity (46 %) as compared to only 58 % and 32 % for undoped catalyst. The advantages on Nd3+ insertion is to enable the formation of required V-P-O compounds and increase the average oxidation number of the catalysts from 4.02 to 4.13. High catalytic performance of VPO was attributed to the large number of actual V4+ phase and high oxygen mobility of the catalysts.